Stop it! Relationship between sport expertise and response inhibition in elite athletes - Fleddermann, Marie-Therese; Reichert, Lukas; Wieland, Björn; Zentgraf, Karen (Frontiers in Psychology, 2023)
The dynamic structure of sport games forces players to make time-sensitive decisions and to initiate actions that may then have to be canceled in response to sudden changes in the game situation. Whether and up to which time already initiated movements can still be inhibited is an important criterion for game performance in elite sport. Research indicates that elite athletes show superior motor inhibition performance compared to recreational athletes. However, no study has examined whether differences also emerge among professional elite athletes themselves. Therefore, this study aimed to investigate whether motor inhibition performance is a differential feature among elite athletes, and whether inhibition performance increases with greater expertise. 106 elite athletes (ice hockey, basketball, volleyball, American football, handball, soccer) completed a PC-based procedure to determine motor inhibition performance using the stop-signal reaction time (SSRT) task for hands and feet (Verbruggen and Logan, 2008). In addition, an expertise score was determined for each elite athlete according to Swann et al. (2015). Multiple linear regression was used to calculate the relationship between expertise and SSRT. Results showed that the expertise score of the elite athletes was between 3.7 and 11.7 out of 16 possible points (MExpertise = 6.8 points, SD = 1.76). The average SSRT of the hands was 224.0 ms (SD = 35.0); of the feet, 257.9 ms (SD = 48.5). Regression results showed a significant relationship between expertise and SSRT (F(2,101) = 9.38, p = .04, R2 = .06). SSRTs of the hands were significant predictors of expertise (b = -.23, t = -2.1, p =.04). Taken together, results suggest that elite athletes with higher expertise outperform elite athletes with lower expertise, indicating that it is possible to differentiate within elite athletes with respect to inhibition performance of the hands. However, whether expertise affects inhibition performance or vice versa cannot be answered at present.